Cosmological insights into the early accretion of r-process-enhanced stars: I. A comprehensive chemodynamical analysis of LAMOST J1109+0754 - Mardini, Mohammad K.; Placco, Vinicius M.; Meiron, Yohai; Ishchenko, Marina; Avramov, Branislav; Mazzarini, Matteo; Berczik, Peter; Arca Sedda, Manuel; Beers, Timothy C.; Frebel, Anna; Taani, Ali; Donnari, Martina; et al. (The astrophysical journal, 2020)
This study presents a comprehensive chemodynamical analysis of LAMOST J1109+0754, a bright (V = 12.8), extremely metal-poor ([Fe/H] = −3.17) star, with a strong r-process enhancement ([Eu/Fe] = +0.94 ± 0.12). Our results are based on the 7D measurements supplied by Gaia and the chemical composition derived from a high-resolution (R ∼ 110,000), high signal-to-noise ratio ( optical spectrum obtained by the 2.4 m Automated Planet Finder Telescope at Lick Observatory. We obtain chemical abundances of 31 elements (from lithium to thorium). The abundance ratios ([X/Fe]) of the light elements (Z ≤ 30) suggest a massive Population III progenitor in the 13.4-29.5 M⊙ mass range. The heavy-element (30 < Z ≤ 90) abundance pattern of J1109+075 agrees extremely well with the scaled-solar r-process signature. We have developed a novel approach to trace the kinematic history and orbital evolution of J1109+0754 with a cOsmologically deRIved timE-varyiNg Galactic poTential (the ORIENT) constructed from snapshots of a simulated Milky Way analog taken from the Illustris-TNG simulation. The orbital evolution within this Milky Way-like galaxy, along with the chemical abundance pattern, implies that J1109+0754 likely originated in a low-mass dwarf galaxy located ∼60 kpc from the center of the Galaxy, which was accreted ∼6-7 Gyr ago, and that the star now belongs to the outer-halo population.